Switching Intention Nasabah Bank Konvensional ke Bank Syariah: Studi Kasus Mahasiswa Ekonomi Islam di Surabaya - Fata Habibullah; Canggih, Clarashinta (Jurnal Ekonomika dan Bisnis Islam, 2025)
The development of Islamic banking in Indonesia shows a positive trend, yet its market share still lags behind conventional banks. This study aims to analyze the factors that influence Islamic Economics students in Surabaya to switch from conventional to Islamic banks. The Push-Pull-Mooring (PPM) framework was employed, covering push factors (price perception, service quality, satisfaction), pull factors (alternative attractiveness), and mooring factors (Islamic financial literacy, religiosity, subjective norms). A quantitative method was applied using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software, involving 162 respondents from three public universities in Surabaya. The results reveal that all push, pull, and mooring variables have a positive and significant influence on switching intention. These findings highlight the role of financial literacy and religious values in motivating the shift toward Islamic financial services among young Muslim generations. This research offers practical implications for Islamic bank marketing strategies to enhance service attractiveness and expand into academic markets.